A method for preparing high-strength elastic carbon aerogel thermal insulation material

By using a combined process of phenol and aldehyde organic monomer, chitosan and bacterial cellulose, a high-strength elastic carbon aerogel thermal insulation material was prepared, which solved the problems of complex process, high cost and low compression strength in the prior art, and achieved the preparation of thermal insulation material with high compression strength and low thermal conductivity.

CN118954483BActive Publication Date: 2025-04-18NAT UNIV OF DEFENSE TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411185473.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-04-18
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

The preparation process of existing carbon aerogel thermal insulation materials is complex, the raw material cost is high, and its compression strength is low, making it difficult to meet the high compression strength and low thermal conductivity requirements in electronic products and aerospace fields.

Method used

Phenol organic monomer and aldehyde organic monomer are used as carbon precursors, combined with chitosan as soft templates and bacterial cellulose, and high-strength elastic carbon aerogel insulation material is prepared through impregnation, hydrothermal, replacement, drying and carbonization cracking processes.

Benefits of technology

The preparation of high-strength elastic carbon aerogel thermal insulation material with simple process and low cost is realized. The compression deformation of the material can reach 80%, the compression strength is between 2.3 and 25.2MPa, and the thermal conductivity is only 0.016 and 0.035W/m·k.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118954483B_ABST
    Figure CN118954483B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a high-strength elastic carbon aerogel thermal insulation material, the purpose of which is to solve the problems of high cost and low compression strength in the current preparation of elastic carbon aerogel thermal insulation materials. The technical scheme is: preparing an organosol by mixing phenol organic monomers, aldehyde organic monomers, chitosan, acetic acid and water; impregnating bacterial cellulose with the organosol by an impregnation process to prepare an organosol / bacterial cellulose composite; preparing an organogel / bacterial cellulose hydrogel by a hydrothermal process; preparing an organogel / bacterial cellulose alcohol gel by a replacement process; preparing an organogel / bacterial cellulose aerogel by a drying process; and preparing a high-strength elastic carbon aerogel thermal insulation material by a carbonization cracking process. The present invention has a simple process, low cost, and is suitable for industrial production. The carbon aerogel thermal insulation material prepared by the present invention has good elasticity, high compression strength, and good thermal insulation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon aerogel preparation technology, and specifically relates to a method for preparing a high-strength elastic carbon aerogel thermal insulation material. Background Art

[0002] Carbon aerogel insulation materials are usually first prepared by polymerizing and cross-linking phenolic and aldehyde organic matter to obtain organic aerogels, and then carbonizing them at high temperature. Its structure is in the shape of a nano "pearl chain", which can have good thermal insulation properties. However, the connection strength between the carbon nanoparticles in this structure is weak and lacks an effective slip system, which makes the carbon aerogel brittle and fragile, and fails prematurely under small compression deformation. Therefore, how to achieve the preparation of carbon aerogel insulation materials with high elasticity (high compression deformation), high compression strength and low thermal conductivity is still an important challenge.

[0003] Carbon aerogels obtained by self-assembly of low-dimensional nanocarbon materials such as one-dimensional nanowires / tubes or two-dimensional graphene as basic structural units can effectively overcome the intrinsic brittleness caused by weak connections between traditional carbon aerogel nanoparticles and show good elasticity. Patent [CN107973283A] discloses a method for preparing elastic carbon aerogels, which first freeze-dries a graphene oxide / nanocrystalline cellulose suspension and then carbonizes it to obtain an elastic carbon aerogel (compression deformation of 99%). However, the intrinsic thermal conductivity of graphene is relatively high (single-layer thermal conductivity 4840-5300 W / m·K), which is not conducive to reducing the thermal conductivity of carbon aerogels; the compressive strength of carbon aerogels is relatively low, less than 0.016 MPa (99% compression deformation); and the cost of graphene raw materials is relatively high. There are similar patents [CN117923903A], [CN115974059A], [CN107686107A], and [CN107456928A], the raw materials are also graphene, the intrinsic thermal conductivity and raw material cost are high, and the compression strength of carbon aerogel is low. Patent [CN114314558A] discloses a method for preparing superelastic carbon aerogel. The invention uses SiO2 nanowire aerogel obtained by oxidation of SiC or Si3N4 as a template, and uniformly coats the surface of the nanowire with pyrolytic carbon / graphite carbon by chemical vapor deposition, and then removes SiO2 by corrosion to prepare a superelastic carbon aerogel with a hollow carbon structure. The carbon aerogel prepared by this method has high elasticity (compression deformation of 98%), but the preparation process is complicated, and the high intrinsic thermal conductivity of graphitized carbon will also reduce the thermal insulation performance of the aerogel. Patent [CN109225152B] discloses a method for preparing ultrafast high adsorption performance cellulose elastic carbon aerogel. The invention obtains freeze-dried bacterial cellulose aerogel by impregnating organic prepolymer, and then drying and carbonizing to obtain elastic carbon aerogel. The method is simple in process and the cost of bacterial cellulose raw materials is low. However, since the carbon aerogel prepared by the invention is mainly used in the adsorption field, the patent does not disclose the compressive strength and thermal conductivity of the carbon aerogel. In addition, the carbon aerogel prepared by the invention is doped with silicon, which will reduce the temperature resistance of the carbon aerogel. Patent [CN106698389A] discloses a method for preparing lignin / bacterial cellulose composite flexible carbon aerogel. The invention soaks bacterial cellulose in a lignin-hydroquinone-formaldehyde solution, and then dries and carbonizes to obtain carbon aerogel. The lignin and bacterial cellulose raw materials used in this method are low in cost, but the compression deformation of the obtained carbon aerogel is small, only 20%. In addition, the carbon aerogel prepared by this invention is mainly used for supercapacitors, so the patent does not disclose the compressive strength and thermal conductivity of the carbon aerogel.The paper published in Chem in 2019 [Biomimetic Carbon Tube Aerogel Enables Super-Elasticity and Thermal Insulation [J]. Chem, 2019, 5 (7): 1871-1882.] used homemade Te nanowires as templates and glucose as a carbon source to prepare carbon nanotube aerogels. The resulting aerogels have low thermal conductivity (0.023 W / m·k) and high elasticity (compression deformation of 90%), but low compression strength of only 0.12 MPa (90% compression deformation), and the preparation process is complicated. Patent [CN111591972A] discloses a method for preparing superelastic hydrophilic all-carbon aerogels. The invention first freeze-dries to obtain an aerogel composed of bacterial cells and bacterial cellulose, and then carbonizes to obtain carbon aerogels. The method has a simple preparation process and uses low-cost bacterial cells and bacterial cellulose raw materials, but the compression strength of the obtained carbon aerogel is relatively low, less than 0.02 MPa (70% compression deformation).

[0004] In summary, the preparation of elastic carbon aerogel insulation materials still has the following problems: the preparation process is complex, the cost of raw materials is high, and the compression strength of carbon aerogel is low (less than 0.2MPa). In the fields of electronic products and aerospace, elastic carbon aerogel insulation materials with high compression strength and low thermal conductivity are urgently needed. Therefore, the low-cost preparation of elastic carbon aerogel insulation materials with low thermal conductivity and high compression strength is still an urgent problem to be solved in this field, which is also the key to realizing the thermal insulation application of elastic carbon aerogel insulation materials. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a high-strength elastic carbon aerogel thermal insulation material in view of the problems of high cost and low compression strength of the currently prepared elastic carbon aerogel thermal insulation material. The method has a simple process and low cost, and the prepared elastic carbon aerogel has high compression deformation and compression strength and low thermal conductivity.

[0006] To achieve the above object, the technical solution of the present invention is as follows:

[0007] The first step is to prepare an organosol by:

[0008] Phenol organic monomer, aldehyde organic monomer, chitosan, acetic acid and water are mixed and stirred evenly to obtain an organic sol, wherein the phenol organic monomer and aldehyde organic monomer are used as carbon precursors; chitosan is required to contain amino groups, as a soft template, reacting with the aldehyde organic monomer to generate a compound containing an imine group, and the chitosans can be cross-linked to form a three-dimensional network structure; water is used as a solvent, acetic acid is used as a catalyst, and the aldehyde organic monomer generates a hydroxymethyl derivative under acid catalysis; chitosan and the hydroxymethyl derivative undergo a polymerization reaction, which can effectively improve the cross-linking density of the reaction network and the three-dimensional network strength of the gel. In the organic sol, the molar ratio of phenol organic monomer, aldehyde organic monomer, acetic acid and water is 1:2:0.03~3.3:50~200; after determining the content of the phenol organic monomer, the mass ratio of the phenol organic monomer to chitosan is 10~100;

[0009] The phenolic organic monomer is phenol or resorcinol;

[0010] The aldehyde organic monomer is formaldehyde or furfural;

[0011] In the second step, the organosol / bacterial cellulose composite is prepared by an impregnation process, the method being:

[0012] The impregnation process uses the organic sol obtained in the first step to impregnate bacterial cellulose at room temperature and pressure for a certain period of time, so that the organic sol enters the bacterial cellulose to obtain an organic sol / bacterial cellulose complex. Among them, bacterial cellulose has high toughness and a developed nanofibrous three-dimensional network structure, which makes it have excellent elasticity and good structural strength; bacterial cellulose molecules contain a large number of hydroxyl functional groups, which can be interconnected with the organic sol through hydrogen bonds, so that the organic sol is coated on the bacterial cellulose, thereby further strengthening the three-dimensional network structure of bacterial cellulose; the organic sol can form a three-dimensional pearl chain-like nano-network in the micron-level gaps of the three-dimensional network structure of bacterial cellulose to divide the micron-level macroporous structure, which can reduce the pore size, reduce thermal conductivity, and support the three-dimensional network structure of the fiber; normal temperature refers to 20-30°C, and normal pressure refers to one atmosphere;

[0013] The bacterial cellulose is a gel-like substance, which is composed of water and bacterial cellulose; the bacterial cellulose content refers to the mass fraction of bacterial cellulose in the gel-like substance, which is 0.03-0.10wt%;

[0014] The immersion time is 6 to 24 hours;

[0015] In the third step, the organogel / bacterial cellulose hydrogel is prepared by a hydrothermal process, wherein:

[0016] The organosol / bacterial cellulose complex is placed in a sealed box, and then placed in a water bath at a constant temperature for a certain period of time, and taken out from the water bath after cooling to room temperature to obtain an organosol / bacterial cellulose hydrogel (still in the sealed box);

[0017] The constant temperature refers to the external heating temperature being controlled at 60-90°C;

[0018] The insulation time is 5 to 72 hours;

[0019] The fourth step is to prepare the organogel / bacterial cellulose alcohol gel by using a replacement process, the method being:

[0020] The organic gel / bacterial cellulose hydrogel obtained in the third step is replaced by anhydrous ethanol for several days, and new ethanol is replaced every day to obtain an organic gel / bacterial cellulose alcohol gel;

[0021] The several days are 3 to 5 days;

[0022] In the fifth step, the organogel / bacterial cellulose aerogel is prepared by a drying process, wherein:

[0023] The organic gel / bacterial cellulose alcohol gel obtained in the fourth step is dried by a drying process to obtain an organic gel / bacterial cellulose aerogel;

[0024] The drying process is carbon dioxide supercritical drying, the drying temperature is 60°C to 70°C, the pressure is 8 to 10 MPa, and the drying time is 12 to 24 hours;

[0025] The sixth step is to prepare a high-strength elastic carbon aerogel insulation material by a carbonization pyrolysis process, the method being:

[0026] The organic gel / bacterial cellulose aerogel obtained in the fifth step is placed in a pyrolysis furnace, evacuated, and after the vacuum degree is less than 100 Pa, heated according to a heating program for carbonization and pyrolysis, and taken out after cooling to room temperature to obtain a high-strength elastic carbon aerogel thermal insulation material;

[0027] The heating program is as follows: the heating rate from room temperature to the maximum temperature of carbonization and cracking is 0.5-10°C / min, the maximum temperature of carbonization and cracking is 700-2000°C, and the insulation time at the maximum temperature of carbonization and cracking is 1-10h.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The process of the present invention is simple and low in cost. In the first step of the present invention, phenol organic monomer and aldehyde organic monomer are used as carbon precursors, acetic acid is used as a catalyst, chitosan is used as a soft template, and water is used as a solvent. The raw materials are directly mixed and uniformly prepared to prepare an organic sol; in the second step, bacterial cellulose is impregnated with the organic sol at room temperature and pressure to obtain an organic sol / bacterial cellulose complex; in the third step, an organic gel / bacterial cellulose hydrogel is obtained through a hydrothermal process; in the fourth step, an organic gel / bacterial cellulose alcohol gel is obtained through a replacement process; in the fifth step, an organic gel / bacterial cellulose aerogel is obtained through a drying process; and in the sixth step, a high-strength elastic carbon aerogel thermal insulation material is obtained through a carbonization and cracking process. The raw materials used in the present invention can all be obtained industrially and are low in price; the main process steps in the entire process flow are the third step, the fifth step, and the sixth step, namely the hydrothermal process, the drying process, and the carbonization and cracking process. The process is simple and suitable for industrial production.

[0030] (2) The high-strength elastic carbon aerogel thermal insulation material prepared by the present invention has good elasticity, high compression strength, and good thermal insulation performance. Its compression deformation can reach 80%, and the compression strength of 80% deformation can reach 2.3-25.2MPa, while the thermal conductivity is only 0.016-0.035W / m·k. In the first step of the present invention, chitosan is used as a soft template, which reacts with aldehyde organic monomers to generate compounds containing imine groups; aldehyde organic monomers can generate hydroxymethyl derivatives under acid catalysis. Chitosan containing imine groups can cross-link with each other to form a three-dimensional network structure, and undergo polymerization reaction with hydroxymethyl derivatives, which can effectively improve the cross-linking density of the reaction network of the gel and the three-dimensional network strength. The second step of the present invention is to use organosol to impregnate bacterial cellulose hydrogel, wherein bacterial cellulose has high toughness and a developed nanofiber-like three-dimensional network structure, so that it has excellent elasticity and good structural strength; bacterial cellulose molecules contain a large number of hydroxyl functional groups, which can be interconnected with organosol through hydrogen bonding, so that the organosol is coated on the bacterial cellulose, thereby further strengthening the three-dimensional network structure of bacterial cellulose; the organosol can form a three-dimensional pearl chain-like nano-network in the micron-level gap of the three-dimensional network structure of bacterial cellulose to divide the micron-level macroporous structure, which can reduce the pore size and thermal conductivity, while supporting the fiber three-dimensional network structure. Finally, an elastic (compression deformation can reach 80%) carbon aerogel insulation material with both high compressive strength (compression strength of 80% deformation can reach 2.3-25.2MPa) and low thermal conductivity (0.016-0.035W / m·k) can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is the overall flow chart of the present invention;

[0032] Figure 2 is a compression strength curve of the high-strength elastic carbon aerogel thermal insulation material (Example 1) prepared by the present invention;

[0033] Figure 3 This is an optical photograph of the high-strength elastic carbon aerogel thermal insulation material (Example 1) prepared by the present invention. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with the accompanying drawings and examples. In the examples, the thermal conductivity and compressive strength of the high-strength elastic carbon aerogel thermal insulation material prepared by the present invention are mainly characterized. Among them, the thermal conductivity of the example is tested using FOX, and the compressive strength is tested using a universal testing machine.

[0035] In the preparation process of high-strength elastic carbon aerogel insulation material, the type of phenol organic monomer, the type of aldehyde organic monomer, the chitosan content, the water content, the acetic acid content and the bacterial cellulose content have an important influence on the thermal conductivity and compressive strength of the high-strength elastic carbon aerogel insulation material. Other indicators only affect the length of the process cycle and have no effect on the thermal conductivity and compression performance of the final high-strength elastic carbon aerogel insulation material. The following discusses the influence of the six key parameters of the type of phenol organic monomer, the type of aldehyde organic monomer, the chitosan content, the water content, the acetic acid content and the bacterial cellulose content on the thermal conductivity and compressive strength of the high-strength elastic carbon aerogel insulation material, and further explains the present invention through examples. The protection scope of the present invention should not be interpreted as being limited to these examples.

[0036] Example 1

[0037] The operation process of preparing Example 1 is as follows Figure 1 As shown, the following steps are included:

[0038] The first step is to prepare an organosol by:

[0039] Resorcinol, formaldehyde, chitosan, acetic acid and water are mixed and stirred to obtain an organosol. The molar ratio of resorcinol, formaldehyde, acetic acid and water is 1:2:3.3:50; the mass ratio of resorcinol to chitosan is 10;

[0040] In the second step, the organosol / bacterial cellulose composite is prepared by an impregnation process, the method being:

[0041] The organic sol obtained in the first step is used to impregnate bacterial cellulose at room temperature and pressure for a certain period of time by an impregnation process, so that the organic sol enters into the bacterial cellulose to obtain an organic sol / bacterial cellulose complex. The bacterial cellulose content is 0.10wt%; the impregnation time is 24h;

[0042] In the third step, the organogel / bacterial cellulose hydrogel is prepared by a hydrothermal process, wherein:

[0043] The organosol / bacterial cellulose complex was placed in a sealed box, and then placed in a water bath at 80° C. for 36 hours, and then taken out after cooling to room temperature to obtain an organosol / bacterial cellulose hydrogel (still in the sealed box);

[0044] The fourth step is to prepare the organogel / bacterial cellulose alcohol gel by using a replacement process, the method being:

[0045] The organic gel / bacterial cellulose hydrogel obtained in the third step is replaced by anhydrous ethanol for 5 days, and the ethanol is replaced once a day to obtain an organic gel / bacterial cellulose alcohol gel;

[0046] In the fifth step, the organogel / bacterial cellulose aerogel is prepared by a drying process, wherein:

[0047] The organic gel / bacterial cellulose alcohol gel obtained in the fourth step is dried by a carbon dioxide supercritical drying process to obtain an organic gel / bacterial cellulose aerogel, wherein the drying temperature is 70°C, the pressure is 10 MPa, and the drying time is 24 hours;

[0048] The sixth step is to prepare a high-strength elastic carbon aerogel insulation material by a carbonization pyrolysis process, the method being:

[0049] The organic gel / bacterial cellulose aerogel is placed in a pyrolysis furnace and evacuated to a vacuum degree of less than 100 Pa. The heating rate from room temperature to the maximum temperature of carbonization pyrolysis is 5°C / min, the maximum temperature of carbonization pyrolysis is 1000°C, and the maximum temperature of carbonization pyrolysis is kept at 1h. The temperature is heated for carbonization pyrolysis, and the furnace is taken out after cooling to room temperature to obtain a high-strength elastic carbon aerogel thermal insulation material.

[0050] Figure 2 This is a compression strength curve of the high-strength elastic carbon aerogel thermal insulation material (Example 1) prepared by the present invention. The horizontal axis is the compression deformation of the high-strength elastic carbon aerogel thermal insulation material, and the vertical axis is the compression strength of the high-strength elastic carbon aerogel thermal insulation material. It can be seen that the compression deformation of the high-strength elastic carbon aerogel thermal insulation material can reach 80%, showing high elasticity. In addition, the high-strength elastic carbon aerogel thermal insulation material has a high compression strength of 25.2MPa at 80% compression deformation.

[0051] Figure 3 This is an optical photograph of the high-strength elastic carbon aerogel thermal insulation material (Example 1) prepared by the present invention. It can be seen that the surface of the high-strength elastic carbon aerogel thermal insulation material is smooth and has no cracks.

[0052] In the second step, when the organosol / bacterial cellulose composite is prepared by the impregnation process, the impregnation time is determined by the bacterial cellulose content. As long as the organosol is immersed in the bacterial cellulose within the set impregnation time, the properties of the prepared high-strength elastic carbon aerogel thermal insulation material are slightly affected; in the third step, when the organosol / bacterial cellulose hydrogel is prepared by the hydrothermal process, the temperature and time are kept in a water bath at a constant temperature for a certain period of time. The temperature and time are determined by the types of raw materials used. The reactivity of different raw materials is different. As long as the gel reaction is fully and completely within the set temperature and time, the properties of the prepared high-strength elastic carbon aerogel thermal insulation material (referring to compressive strength, thermal conductivity, elasticity) are slightly affected; in the fourth step, when the organosol / bacterial cellulose hydrogel is prepared by the replacement process, the organosol / bacterial cellulose hydrogel is kept in a water bath at a constant temperature for a certain period of time. The temperature and time are determined by the types of raw materials used. The reactivity of different raw materials is different. As long as the gel reaction is fully and completely within the set temperature and time, the properties of the prepared high-strength elastic carbon aerogel thermal insulation material (referring to compressive strength, thermal conductivity, elasticity) are slightly affected. When the organic gel / bacterial cellulose alcohol gel is replaced for several days, the replacement time is determined by the water content. As long as the replacement is complete within the set replacement time, the properties of the prepared high-strength elastic carbon aerogel thermal insulation material are slightly affected; in the fifth step of the drying process for preparing the organic gel / bacterial cellulose aerogel, as long as the liquid in the gel is dried within the set temperature, pressure and time, the properties of the prepared high-strength elastic carbon aerogel thermal insulation material are slightly affected; in the sixth step of the carbonization and pyrolysis process for preparing the high-strength elastic carbon aerogel thermal insulation material, the carbonization and pyrolysis temperature and time determine the carbonization and pyrolysis degree of bacterial cellulose and organic aerogel, as long as the bacterial cellulose and organic aerogel are completely carbonized and pyrolyzed into carbon aerogel. The above conditions have no effect on the compressive strength, thermal conductivity and elasticity of the high-strength elastic carbon aerogel thermal insulation material. Therefore, the process parameters used in Examples 2 to 324 are shown in Table 1, and the experimental process parameters not listed in the table are the same as those in Example 1.

[0053] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any changes made by adopting the design principle of the present invention and by non-creative labor on this basis shall fall within the scope of protection of the present invention. In the organic sol prepared in the first step, the molar ratio of phenol organic monomer, aldehyde organic monomer, acetic acid and water is 1:2:0.03-3.3:50-200; based on the content of phenol organic monomer, the mass ratio of phenol organic monomer to chitosan is 10-100; the content of bacterial cellulose is 0.03-0.10wt%;

[0054] Table 1 Preparation process parameters and material performance parameters of the present invention

[0055]

[0056]

[0057]

[0058]

[0059]

[0060]

[0061]

[0062]

[0063]

[0064]

[0065]

[0066]

Claims

1. A method for preparing a high-strength elastic carbon aerogel thermal insulation material, characterized in that The following steps are involved: The first step is to prepare an organosol by: Phenol organic monomer, aldehyde organic monomer, chitosan, acetic acid and water are mixed and stirred to obtain an organic sol, wherein the phenol organic monomer and the aldehyde organic monomer are used as carbon precursors; chitosan is required to contain amino groups, as a soft template, reacting with the aldehyde organic monomer to generate a compound containing an imine group, and the chitosans are cross-linked to form a three-dimensional network structure; water is used as a solvent, acetic acid is used as a catalyst, and the aldehyde organic monomer generates a hydroxymethyl derivative under acid catalysis; chitosan and the hydroxymethyl derivative undergo a polymerization reaction to increase the cross-linking density of the reaction network and the three-dimensional network strength of the gel; in the organic sol, the molar ratio of the phenol organic monomer, the aldehyde organic monomer, the acetic acid and the water is 1:2:0.03-3.3:50-200; after determining the content of the phenol organic monomer, the mass ratio of the phenol organic monomer to the chitosan is 10-100; In the second step, the organosol / bacterial cellulose composite is prepared by an impregnation process, the method being: The organic sol obtained in the first step is used to impregnate bacterial cellulose at room temperature and pressure for a certain period of time by an impregnation process, so that the organic sol enters the bacterial cellulose to obtain an organic sol / bacterial cellulose complex; the bacterial cellulose has high toughness and a nanofiber-like three-dimensional network structure, and the bacterial cellulose molecules contain hydroxyl functional groups, which are interconnected with the organic sol by hydrogen bonding, so that the organic sol is coated on the bacterial cellulose to strengthen the three-dimensional network structure of the bacterial cellulose; the organic sol forms a three-dimensional pearl chain-like nano-network in the micron-level gaps of the three-dimensional network structure of the bacterial cellulose to divide the micron-level macroporous structure, reduce the pore size, reduce the thermal conductivity, and support the three-dimensional network structure of the fiber; The bacterial cellulose is a gel-like substance composed of water and bacterial cellulose; the bacterial cellulose content is 0.03-0.10wt%; In the third step, the organogel / bacterial cellulose hydrogel is prepared by a hydrothermal process, wherein: The organosol / bacterial cellulose complex is placed in a sealed box, and then placed in a water bath at a constant temperature for a certain period of time, and taken out from the water bath after cooling to room temperature to obtain an organosol / bacterial cellulose hydrogel; The fourth step is to prepare the organogel / bacterial cellulose alcohol gel by using a replacement process, the method being: The organic gel / bacterial cellulose hydrogel obtained in the third step is replaced by anhydrous ethanol for 3 to 5 days, and new ethanol is replaced every day to obtain an organic gel / bacterial cellulose alcohol gel; In the fifth step, the organogel / bacterial cellulose aerogel is prepared by a drying process, wherein: The organic gel / bacterial cellulose alcohol gel obtained in the fourth step is dried by a drying process to obtain an organic gel / bacterial cellulose aerogel; The sixth step is to prepare a high-strength elastic carbon aerogel insulation material by a carbonization pyrolysis process, the method being: The organic gel / bacterial cellulose aerogel obtained in the fifth step is placed in a pyrolysis furnace and evacuated. After the vacuum degree is less than 100 Pa, the furnace is heated according to a heating program for carbonization and pyrolysis. The furnace is cooled to room temperature and then taken out to obtain a high-strength elastic carbon aerogel thermal insulation material.

2. The method for preparing a high-strength elastic carbon aerogel thermal insulation material according to claim 1, characterized in that In the first step, the phenol organic monomer is phenol or resorcinol; and the aldehyde organic monomer is formaldehyde or furfural.

3. The method for preparing a high-strength elastic carbon aerogel thermal insulation material according to claim 1, characterized in that The normal temperature in the second, third and sixth steps refers to 20-30° C., and the normal pressure in the second step refers to one atmosphere.

4. The method for preparing a high-strength elastic carbon aerogel thermal insulation material according to claim 1, characterized in that The second step of dipping for a certain period of time is 6 to 24 hours.

5. The method for preparing a high-strength elastic carbon aerogel thermal insulation material according to claim 1, characterized in that In the second step, the bacterial cellulose is impregnated with the organosol obtained in the first step at room temperature and pressure for 6 to 24 hours.

6. The method for preparing a high-strength elastic carbon aerogel thermal insulation material according to claim 1, characterized in that The constant temperature in the third step means that the external heating temperature is controlled at 60-90° C.; the insulation time is 5-72 hours.

7. The method for preparing a high-strength elastic carbon aerogel thermal insulation material according to claim 1, characterized in that The drying process in the fifth step is supercritical carbon dioxide drying, the drying temperature is 60° C. to 70° C., the pressure is 8 to 10 MPa, and the drying time is 12 to 24 hours.

8. The method for preparing a high-strength elastic carbon aerogel thermal insulation material according to claim 1, characterized in that The heating program in the sixth step is a heating rate of 0.5-10°C / min from room temperature to the maximum temperature of carbonization and cracking, the maximum temperature of carbonization and cracking is 700-2000°C, and the holding time at the maximum temperature of carbonization and cracking is 1-10h.

Citation Information

Patent Citations

  • Graphene / sodium alga acid / carbon nano tube compound elastic aerogel applied in strain sensor and preparation method of graphene / sodium alga acid / carbon nano tube compound elastic aerogel

    CN107456928A

  • Preparation method of elastic hydrophobic carbon nano tube and graphene compound aerogel

    CN107686107A

  • Elastic carbon aerogel as well as preparation method and application thereof

    CN107973283A

  • An ultrafast, high-adsorption-performance cellulose elastic carbon aerogel, its preparation method, and its applications.

    CN109225152B

  • Hyperelastic hydrophilic all-carbon aerogel and preparation method thereof

    CN111591972A